A comparison of the effect of bi-level positive airway pressure and synchronized intermittent mandatory ventilation in preterm infants with respiratory distress syndrome. (12th December 2022) - Lin, Xin; Yang, Changyi
Abstract: Objective: Bi-level positive airway pressure (BiPAP) and synchronized intermittent mandatory ventilation (SIMV) can be used to achieve peak inspiratory pressure and positive end-expiratory pressure to avoid alveolar collapse and improve oxygenation in preterm infants during the treatment of respiratory distress syndrome (RDS), and there is an urgent demand for evaluating the effects and prognoses of these two ventilation modes. Study design: We conducted a retrospective study on preterm infants (≤32 weeks and <2500 g) from March 2015 to March 2020 with BiPAP ( n  = 63) and SIMV ( n  = 63). The primary outcomes were successful treatment and weaning within 72 h, the demand for a second pulmonary surfactant supply and the need for a second respiratory support. The secondary outcome was the incidence of complications. Results: There were no significant differences ( p  > .05) in the primary outcomes or the incidence of complications (pneumonia, apnea, respiratory failure, air leak syndrome, persistence of patent ductus arteriosus, neonatal sepsis, necrotizing enterocolitis, retinopathy of prematurity, and intraventricular hemorrhage). There were significant differences ( p  < .05) in the incidence of pulmonary hemorrhage, bronchopulmonary dysplasia and IVH (≥grade II). Conclusions: Although both BiPAP and SIMV achieved good early treatment outcomes of RDS in preterm infants, BiPAP support is recommended for reducing the incidence of pulmonary hemorrhage, bronchopulmonary dysplasia and IVH (≥grade II) if infants are tolerant. Attempts should be made to prevent these complications from happening with the use of SIMV support if infants are intolerant.